2010
DOI: 10.1007/s12275-009-0176-9
|View full text |Cite
|
Sign up to set email alerts
|

Anti-HIV-1 efficacy of extracts from medicinal plants

Abstract: The anti-HIV-1 activities of butanol, hexane, chloroform and water extracts from four widely used folk medicinal plants (Sophora flavescens, Tulipa edulis, Herba ephedra, and Pachyma hoelen Rumph) were evaluated in this study. The hexane extract of Pachyma hoelen Rumph, PH-4, showed effective inhibition against HIV-1. The 50% effective concentration (EC(50)) of PH-4 was 37.3 microg/ml in the p24 antigen assay and 36.8% in the HIV-1 recombinant RT activity test (at 200 microg/ml). In addition, the PH-4 showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…14) Polysaccharides and phlorotannins isolated from the marine algae show distinct inhibitory activity against HIV-1 reproduction as well as viral infection. 15,16) In our present research, we reported the anti-HIV-1 activity of phloroglucinol derivative 8,4‴-dieckol from marine brown alga, Ecklonia cava. The results obtained from the experiments indicated that 8,4‴-dieckol inhibited the cytopathic effects of HIV-1 including HIV-1 induced syncytia formation, lytic effects, and viral p24 antigen production, as well as exhibited RT enzyme inhibitory and HIV-1 entry activities.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…14) Polysaccharides and phlorotannins isolated from the marine algae show distinct inhibitory activity against HIV-1 reproduction as well as viral infection. 15,16) In our present research, we reported the anti-HIV-1 activity of phloroglucinol derivative 8,4‴-dieckol from marine brown alga, Ecklonia cava. The results obtained from the experiments indicated that 8,4‴-dieckol inhibited the cytopathic effects of HIV-1 including HIV-1 induced syncytia formation, lytic effects, and viral p24 antigen production, as well as exhibited RT enzyme inhibitory and HIV-1 entry activities.…”
mentioning
confidence: 79%
“…Five microliters of viral lysate was transferred to each well of a 96-well microtiter plate containing indicated concentrations of test compound or nevirapine as a positive control. Twenty microliters of reaction mixture containing a template/primer hybrid, poly(A)/d(T) 16 , and dTTP as a triphosphate substrate was added to the wells and the plate was incubated for 1 h at 37°C. Two microliters of 200 mM EDTA was added to each well to terminate the polymerization reaction.…”
Section: Western Blot Analysismentioning
confidence: 99%
“…E. sinica has been used in traditional Chinese medicine for >2000 years(Abourashed et al, 2003). The pharmacological effects of E. sinica include its antimicrobial, antifungal and antioxidant(Parsaeimehr et al, 2010); antiviral(Lee et al, 2010); anti- inflammatory (Kim et al, 2010) and anti-asthmatic activities(Chaitanya et al, 2014). The relaxant effect of E. sinica on tracheal smooth muscles was investigated.…”
mentioning
confidence: 99%
“…The top two TCM compounds can be selected (Table 1). These TCM compounds, (S)-cathinone and (1S,2S)-norpseudoephedrine selected from TCM database, are both extracted from the herb Ephedra sinica stapf which was defined as anti-HIV herb [5961]. Cathinone has reported the function for HIV [62] and immunity [63].…”
Section: Resultsmentioning
confidence: 99%